Role of symposia to enhance active learning compared to conventional lectures among MBBS students - Usha KK; Haseena KA; Santosh Balakrishnan; Sathidevi VK (Asian Journal of Medical Sciences, 2022)
Background: Symposium as a large group teachinglearning method ensures active participation from students compared to conventional lectures. Competency-based curriculum lays emphasis on student-centered learning. The number of students who join medical colleges to pursue MBBS increase each year. At the same time, infrastructure and faculty strength do not change much. Though small group teaching is preferred student-centered method, other teachinglearning methods can be modified accordingly.